The ovalbumin gene: cloning and molecular organization of the entire natural gene. - Dugaiczyk, A (1979)
We report the analyses of recently cloned restriction fragments of the natural ovalbumin gene that overlap in part with previously cloned DNA fragments but extend further into the flanking sequences of the gene. These clones now permit us to identify the DNA sequence that codes for the 5' end of ovalbumin mRNA. Based on these and previous results, the molecular organization of the entire ovalbumin gene was established. The entire gene is composed of eight structural DNA sequences separated by seven intervening sequences that are not present in the mature mRNA. In addition, an ovalbumin gene clone has been obtained from a chicken gene library. Analysis of DNA isolated from this particular clone by molecular hybridization and electron microscopic mapping revealed that it contains the entire ovalbumin gene a single segment of DNA and its structure was consistent with that predicted from our physical map constructed from individually cloned fragments of the gene.